2008
DOI: 10.1136/hrt.2007.122622
|View full text |Cite
|
Sign up to set email alerts
|

Infarct size by contrast enhanced cardiac magnetic resonance is a stronger predictor of outcomes than left ventricular ejection fraction or end-systolic volume index: prospective cohort study

Abstract: Infarct size, EF and ESVI can predict the development of future cardiac events. Acute infarct size, which is independent of LV stunning and loading, directly relates to LV remodelling and is a stronger predictor of future events than measures of LV systolic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
263
2
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(286 citation statements)
references
References 30 publications
12
263
2
9
Order By: Relevance
“…MI size,4, 5 presence of microvascular obstruction (MVO),6, 7 and myocardial salvage8, 9 assessed by cardiovascular magnetic resonance (CMR) performed in the first few days after reperfusion in STEMI patients have all been shown to be strong predictors of adverse left ventricular (LV) remodeling and development of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…MI size,4, 5 presence of microvascular obstruction (MVO),6, 7 and myocardial salvage8, 9 assessed by cardiovascular magnetic resonance (CMR) performed in the first few days after reperfusion in STEMI patients have all been shown to be strong predictors of adverse left ventricular (LV) remodeling and development of heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Several pathophysiologic mechanisms have been suggested, nevertheless there is paucity of clinical markers that can characterize a hemodynamic milieu predictive of the risk of cardiac remodeling either following infarction (Nijveldt et al, 2009;Wu et al, 2008) or excessive sport activity (De Luca et al, 2011;Mihl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5,[14][15][16] In our study population, the strongest relationship between total infarct size and LVEF (r = -0.79, P < 0.01) was found in early revascularized patients (n = 10) with an infarct size ≥ 15% of the LV mass. This was also recently shown by Pride, et al, who found a similar relationship in MI patients with an infarct size ≥ 15% (r = -0.81, P < 0.001).…”
Section: Discussionmentioning
confidence: 85%
“…9) However, most previous CE-CMR studies that investigated the relationship between infarct size and cardiac remodeling did not measure the size of the peri-infarct zone. [2][3][4][5][6]8,9,[14][15][16]18,19) The only exception was a study by Heidary,et al,17) who found in a population of patients with ischemic cardiomyopathy, no significant relation between infarct tissue characteristics (including peri-infarct size) and both LV geometry and function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation